Detection of disk drug orientation for disk diffusion susceptibility testing - Okowat, Thitikarn; Taertulakarn, Somchat; Samosornsuk, Seksun; Pintavirooj, Chuchart (My University, 2011)
At the present, the microbiological infection is one of the most significant issues in the global. The medical laboratory diagnosis, microbiology, is the most popular way to identify a type of microbiology which is infected-source. Moreover, there are a few microbial prognoses to support a medical treatment. It is effectively controlled by antibiotic management such as Disk diffusion antimicrobial susceptibility testing, Kirby Bauer AST. This technique is well-known in all microbiological laboratories. This study was the development of interpreting system for antimicrobial susceptibility testing by the disc diffusion technique with automatically measures and interprets inhibition zone diameter. The operated system has comprised electronic part; optical devices, video capture part, and software which manages and analyses all processes. The technology of this system was uncomplicated, effective cost and potential automated test. The disk detected-process and measured process; pre-process, were operated via image processing steps such as image smoothening, edge detection, template matching. The output of this part was sent to the next sections, data correction, interpretation and report, respectively. © 2011 IEEE.
Keywords: Antimicrobial Susceptibility Testing; Disk Diffusion Technique; Image Processing